Depression and Peer-Relationship among Adolescents in Haryana. (1st April 2016) - Chopra, Rupika; Punia, Shakuntla; Sangwan, Santosh
Abstract: Depression is a psychological problem or condition that changes how one thinks and feels, and also affects social behavior and sense of physical wellbeing. The present study was undertaken on 460 adolescents of 11 th and 12 th grade, that is, 112 studying in university and 348 studying in the government school of the Hisar district of Haryana state falling in age group of 16 to 17 years. The Peer-Relationship Questionnaire (PRQ) was used to assess the peer-relationship and the Children Depression Inventory (CDI) was used to assess the depression status. Results of the study highlighted that university adolescents were more depressed as compared to school adolescents and two aspects of peer-relationship, that is bullying and victimization were positively and significantly correlated with depression whereas another aspect that is pro-social behavior was negatively as well as significantly correlated with depression.